2012
DOI: 10.1016/j.jacc.2011.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Safety of Dabigatran Versus Warfarin for Periprocedural Anticoagulation in Patients Undergoing Radiofrequency Ablation for Atrial Fibrillation

Abstract: In patients undergoing AF ablation, periprocedural dabigatran use significantly increases the risk of bleeding or thromboembolic complications compared with uninterrupted warfarin therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
185
2
11

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 287 publications
(205 citation statements)
references
References 32 publications
7
185
2
11
Order By: Relevance
“…Data comparing uninterrupted dabigatran versus warfarin have shown contrasting results and have included mainly paroxysmal AF patients [6][7][8][9][10][11]. When non-paroxysmal AF patients have been included, uninterrupted dabigatran use seemed to be inferior when compared to the uninterrupted warfarin use in protecting against TIA/stroke [12,13].…”
mentioning
confidence: 99%
“…Data comparing uninterrupted dabigatran versus warfarin have shown contrasting results and have included mainly paroxysmal AF patients [6][7][8][9][10][11]. When non-paroxysmal AF patients have been included, uninterrupted dabigatran use seemed to be inferior when compared to the uninterrupted warfarin use in protecting against TIA/stroke [12,13].…”
mentioning
confidence: 99%
“…Lakkireddy et al discontinued dabigatran on the morning of the procedure. 5 In other words, AF procedures were performed within approximately 1.5-fold of the elimination half-life, suggesting a significant residual pharmacodynamic effect. In this regard, Winkle et al 6 recently demonstrated that periprocedural use of dabigatran caused no bleeding and thromboembolic complications until 30 days after the procedure.…”
Section: Article P 2337mentioning
confidence: 99%
“…In patients whose eGFR was <40 ml · min -1 · 1.73 m −2 , it was stopped 60 h before ablation. Thus, when compared with the study by Lakkireddy et al, 5 Winkle et al discontinued dabigatran earlier before the ablation procedure. 6 The target range of the activated clotting time (ACT) during the ablation procedure is another important factor.…”
Section: Article P 2337mentioning
confidence: 99%
See 2 more Smart Citations